2023
DOI: 10.2147/jmdh.s391917
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality Among Children with Confirmed and Suspected Cases of COVID-19 in East Java, Indonesia

Abstract: Introduction Coronavirus disease 2019 (COVID-19) increases rapidly and causes mortality in all groups, including children. However, the predictive risk factors of mortality among children remain inconclusive. This study aimed to analyse the predictors related to mortality among children with COVID-19. Methods Secondary data analysis was conducted using provincial COVID-19 data from April 2020 to May 2021. We selected 6441 children under age 18 to be included in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…To confirm the above-mentioned facts about the factors influencing mortality in children with COVID-19, Efendi et al (17) pointed to underlying diseases, such as heart disease, laboratory measurements, and clinical manifestations. In this regard, preventive measures and systematic management strategies are needed to improve outcomes in children with heart disease (20) and the extent to which markers are monitored.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To confirm the above-mentioned facts about the factors influencing mortality in children with COVID-19, Efendi et al (17) pointed to underlying diseases, such as heart disease, laboratory measurements, and clinical manifestations. In this regard, preventive measures and systematic management strategies are needed to improve outcomes in children with heart disease (20) and the extent to which markers are monitored.…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, Flaxman et al (5) in 2023 found 1 person per 100,000 across all age groups, about 4 children under 1 year, 0.6 in children from 1 to 4 years, 0.4 for children from 5 to 9 years, 0.5 for children from 10 years to 14 years, and 1.8 per 100,000 for children aged 15 -19 years. Efendi et al (17) reported that several factors, such as age, treatment, disease severity, and underlying medical conditions, had a significant effect on the mortality rate of children with COVID-19. In this way, it is possible that as age increases, the risk of dying from COVID-19 will decrease.…”
Section: Discussionmentioning
confidence: 99%
“…In North America, mortality was higher in children younger than one year old and then in adolescents between 15 and 19 years of age [14]. In 2021 and 2022, another study in Java, Indonesia analyzed 6441 under 18-year-old patients positive for COVID-19 and reported 2.7% of deaths with other associated factors [15].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of predictors of COVID-19 severity in children is essential for improving clinical management and outcomes in this vulnerable population [6]. Several studies have evaluated predictors of severe COVID-19 in adults, including age, comorbidities, and biomarkers such as D-dimer and C-reactive protein [7].…”
Section: Introductionmentioning
confidence: 99%